Szerbia határon átnyúló együttműködésének földrajzi sajátosságai az EUkülső határán: GEOGRAPHICAL CHARACTERISTICS OF SERBIA’S CROSS-BORDER COOPERATION AT THE EXTERNAL BORDER OF THE EU - Nagy, Imre (Közép-Európai Közlemények, 2020)
The article presents the territorial features of Serbia’s cross-border cooperation with neighboring EU countries. It refers to the various network types between municipalities/settlements within a single project programme and at the level of all other analysed border programmes in the EU border regions that are components of the European Territorial Cooperation. It also shows examples of prosperous cross-border networks (Serbia–Hungary, Serbia–Croatia, Serbia–Romania, Serbia–Bulgaria) of interested communities: what positions they have and what the weight of the border settlements is in the network of cooperation in a horizontal sense. Furthermore, it discusses differences of network types of cross-border cooperation of municipalities based on financial assistance from the EU, the IPA[i] funds (2007–2013) in Serbia as a border region at the external border of the EU. The paper tries to define its spatial differentiation based on the number of applications and the amount of financial aid.